Impact of capital gains taxation on the holding period of investments under different tax systems - Annika Hegemann; Angela Kunoth; Kristina Rupp; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
An investment that is characterized by exit flexibility requires both decisions on investment and holding period. As selling an investment often leads to tax-liable capital gains and capital gains crucially depend on the duration of an investment we investigate the impact of capital gains taxation on the holding period under three different tax systems. In our analytical investigation we examine whether there is an optimal exit time and if there is no optimal exit time, what would be an appropriate time of sale. Moreover, we determine the worst exit time which should be avoided by investors. We find that while often an immediate sale is optimal longer holding periods may be beneficial under certain conditions. Beyond the well-known impact of the retention policy we clarify that the minimal holding period particularly depends on the degree of income and corporate tax integration. We find, e.g., a high retention rate to extend the minimum holding period under a shareholder relief tax system but is likely to accelerate sales under a classic corporate tax system. These results help to anticipate the economic implications of capital gains taxes on investment. Obviously, depending on the underlying tax system the after-tax profitability of long-term and sustainable investments is particularly affected by capital gains taxes. These results are interesting for both investors and tax politicians.
Keywords: H20; H21; H25; 330; Capital Gains Taxation; Holding Period; Exit Flexibility; Investment Decisions; Timing Decisions